Passive acoustic monitoring predicts daily variation in North Atlantic right whale presence and relative abundance in Roseway Basin, Canada. Issue 4 (8th April 2019) - Durette‐Morin, Delphine; Davies, Kimberley T. A.; Johnson, Hansen D.; Brown, Moira W.; Moors‐Murphy, Hilary; Martin, Bruce; Taggart, Christopher T.
Abstract: North Atlantic right whale monitoring in Roseway Basin, Canada, is primarily based on short‐term (<14 d) visual surveys conducted during August–September. Variability in survey effort has been the biggest limiting factor to studying changes in the population's occurrence and habitat use. Such efforts could be enhanced considerably using passive acoustic monitoring (PAM). We sought to determine if variation in whale presence, relative abundance, demography, and/or behavior (estimated through visual surveys) could be explained by variation in three right whale call types in this habitat. A generalized linear model was fit to 23 d of concurrent PAM and visual monitoring during four summers within the Roseway Basin Right Whale Critical Habitat boundaries. The model revealed significant positive relationships between relative abundance, call counts and presence of surface‐active group behavior. PAM can refine daily right whale presence estimates. While visual observations ( n = 23 d) implied a 40% decline in right whale presence during 2014–2015 relative to 2004–2005, PAM data ( n = 211 d) showed right whales were present between 71%–85% of survey days throughout all years analyzed. We demonstrate that PAM is a useful tool to extend periods of right whale monitoring, especially in areas where visual monitoring efforts may be limited.